Differential linkage of triglyceride and glucose levels on rat chromosome 4 in two segregating rat populations - Seda, O; Liska, F; Krenová, D; Kazdová, L; Sedová, L; Zima, T; Peng, J; Tremblay, J; Kren, V; Hamet, P (Folia biologica, 2003)
The PD/Cub is a recently established model of the IRS. The BN.SHR4 congenic strain was derived by introgression of the chromosome 4 segment of SHR origin (including the defective Cd36/Fat allele) onto the BN/Cub genetic background. We investigated the linkage of metabolic and morphometric phenotypes (total body weight, OGTT, fasting serum levels of TG, FFA) on chromosome 4 in two separate F2 rat populations: the PD/Cub x BN/Cub and PD/Cub x BN.SHR4 (total N = 243). In the PD/Cub x BN.SHR4 F2s, we found significant linkage for fasting TG levels (LOD = 3.26) and suggestive linkage for fasting glycaemia (LOD = 2.80) in the interval Il-6 - D4Bro1, i.e. the part of chromosome 4 of SHR origin in the BN.SHR4 congenic. However, no linkage for fasting TG concentrations, fasting glycaemia or any other followed parameter was found in the second, PD/Cub x BN/Cub F2. The differential linkage of TG and glucose levels to the centromeric part of rat chromosome 4q in the studied F2s points to the importance of this region for the lipid and carbohydrate metabolism at the specific age (10 months) and diet (standard chow) combination. The Cd36/Fat and Il-6 genes are the preliminary positional candidates for the observed effect.
Keywords: inbrední kmeny potkanů; Rats, Inbred Strains; glukosa; Rats; Triglycerides; krevní glukóza; Genetic Linkage; plocha pod křivkou; genetická vazba; krysa rodu Rattus; Blood Glucose; zvířata; mapování chromozomů; triglyceridy; Chromosome Mapping; Hybridization, Genetic; hybridizace genetická; Area Under Curve; Glucose; Animals